AMPK phosphorylates NAMPT to regulate NAD+ homeostasis under ionizing radiation. Issue 10 (5th October 2022) - Liao, Xiaoyu; Huang, Xiaoke; Li, Xin; Qiu, Xuemei; Li, Mi; Liu, Rui; He, Tao; Tang, Qingfeng
Abstract : Abstract : Radiation-induced oral mucositis is the most common complication for patients who receive head/neck radiotherapy. Nicotinamide adenine dinucleotide (NAD + ) is vital for DNA damage repair under ionizing radiation, through functioning as either the substrate for protein poly(ADP-ribosyl)ation at DNA break sites or the cofactor for multiple DNA repair-related enzymes, which therefore can result in a significant consumption of cellular NAD + during DNA repair. Mammalian cells produce NAD + mainly by recycling nicotinamide via the salvage pathway, in which the rate-limiting step is governed by nicotinamide phosphoribosyltransferase (NAMPT). However, whether NAMPT is co-opted under ionizing radiation to timely fine-tune NAD + homeostasis remains elusive. Here we show that ionizing radiation evokes NAMPT activation within 30 min without apparent changes in its protein expression. AMPK rapidly phosphorylates NAMPT at S314 under ionizing radiation, which reinforces the enzymatic activity of NAMPT by increasing NAMPT binding with its substrate phosphoribosyl pyrophosphate (PRPP). AMPK-mediated NAMPT S314 phosphorylation substantially restores NAD + level in the irradiated cells and facilitates DNA repair and cell viability. Our findings demonstrate a new post-translational modification-based signalling route, by which cells can rapidly orchestrate NAD + metabolism to support DNA repair, thereby highlighting NAMPT as a potential target for the prevention of ionizing radiation-induced injuries.